2013
DOI: 10.1007/s00442-013-2787-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in plant volatile emission does not result in differential attraction of natural enemies in the field

Abstract: Volatile organic chemical (VOC) emission by plants may serve as an adaptive plant defense by attracting the natural enemies of herbivores. For plant VOC emission to evolve as an adaptive defense, plants must show genetic variability for the trait. To date, such variability has been investigated primarily in agricultural systems, yet relatively little is known about genetic variation in VOCs emitted by natural populations of native plants. Here, we investigate intraspecific variation in constitutive and herbivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…Paralleling our results, Wason, Agrawal and Hunter () recently showed that high‐latitude populations of Asclepias syriaca showed greater induction of VOCs emissions than low‐latitude ones. However, using the same system, despite this difference in VOCs produced by plants from different latitudes, Wason and Hunter () found no difference in recruitment of herbivore natural enemies between ecotypes. In contrast, here, we found increased ant attraction to the high‐elevation ecotype of V. sepium following induction with methyl‐jasmonate.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Paralleling our results, Wason, Agrawal and Hunter () recently showed that high‐latitude populations of Asclepias syriaca showed greater induction of VOCs emissions than low‐latitude ones. However, using the same system, despite this difference in VOCs produced by plants from different latitudes, Wason and Hunter () found no difference in recruitment of herbivore natural enemies between ecotypes. In contrast, here, we found increased ant attraction to the high‐elevation ecotype of V. sepium following induction with methyl‐jasmonate.…”
Section: Discussionmentioning
confidence: 97%
“…Relatively few studies have reported intraspecific variation in VOCs emission in natural populations of plants and/or differences in the attraction of natural enemies (Kessler, Gase & Baldwin ; Kariyat et al . ; Pearse, Gee & Beck ; Wason & Hunter ). Yet, we know that the production of herbivore‐induced VOCs depends on the interaction between biotic factors, including plant hormones (van Poecke & Dicke ), herbivore‐derived elicitors (Halitschke et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition of herbivore‐induced VOC blends is known to be highly specific to plant genotype (e.g., Degen et al. , Wason and Hunter ), plant sex (e.g., Ashman ), and herbivore identity (Clavijo McCormick et al. , Moreira et al.…”
Section: Introductionmentioning
confidence: 99%
“…Many parasitoids are generalists and attack multiple hosts, while many herbivorous insects feed on a variety of plants (Ali and Agrawal 2012); this is problematic when coupled with the fact that some plants release odors that are specific to the type of herbivore attacking them (De Moraes et al 1998). Additionally, there is variation in VOC production even among individuals in populations of plants (Dicke and Baldwin 2010, Wason and Hunter 2013). Considering all of this variability together, how do parasitoids ever find hosts?…”
mentioning
confidence: 99%